(untitled) (Journal of Astronomy & Earth Sciences Education, 2018)
A new survey for measuring students’ astronomy and science attitudes that has been validated for use with high school students (with a future intent to expand to middle school and university) is presented. We initially present a short review of instruments in the literature that attempt to measure attitudes in astronomy together with the difficulties encountered in measuring these by researchers in the subsequent analyses of results. To illustrate this, we present an example from an Astro101-level university course to display the problems with the current, most commonly used, astronomy attitude instrument. We then present the initial design and the Factor Analysis of a new instrument designed to address the deficiencies of this existing instrument from a sample of students in a high school-level astronomy education project. The factors identified by this instrument include: Interest in Astronomy, Interest in Science Outside of School, Practical Work in Science, Teacher’s Actions in science, Perceptions of Ability in Science, Future Aspirations in Science, Benefits of Science, and Personal Relevance of School Science, all of which possess high internal response consistency and construct validity.